“Good For You and Good To You": The Importance of Emphasizing Race when Radicalizing Students around the Food Movement - Burdick, John M. (Radical Teacher, 2014)
While there is great radical and anti-capitalist potential within the “Food Movement,” it can often be undermined by foodie culture’s attachment to a problematic racial politics in which white, urban and middle/upper classed subject positions are articulated through romanticized attachments to local and organic foodways, attachments that at times unconsciously echo nativist and settle colonial sentiments. These problematic racial logics limit the food movement’s ability to fully address the ways by which the corporate domination of the food system disproportionally impacts low-income communities and communities of color. This article contends that food educators must fundamentally rewrite and reshape the very foundations of our food pedagogy to forefront the ways by which the food system is and always has been driven by the exploitation of bodies of color, the forced removal of Indigenous peoples from their homelands and the ways by which food access continues to be predicated on systems of power that perpetuate racial genocide. Drawing upon the experiences from a unit taught on “soul food” in an undergraduate course on the U.S. Food System, this article offers pedagogical strategies and innovative interdisciplinary methodological approaches to teaching the race based apartheid within the American food system and role of race within contemporary food justice movements. As such, this article will contend that conversations with students on soul food, and a race-centered analysis of the food system, ultimately result in a more radical food consciousness, one that is not just located in food related issues, but also grounded in a foundational critique of the complex hierarchal systems of power and oppression that drive American society.